2020
DOI: 10.1155/2020/8817419
|View full text |Cite
|
Sign up to set email alerts
|

A New Kinect-Based Posture Recognition Method in Physical Sports Training Based on Urban Data

Abstract: Physical data is an important aspect of urban data, which provides a guarantee for the healthy development of smart cities. Students’ physical health evaluation is an important part of school physical education, and postural recognition plays a significant role in physical sports. Traditional posture recognition methods are with low accuracy and high error rate due to the influence of environmental factors. Therefore, we propose a new Kinect-based posture recognition method in a physical sports training system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This experiment performs 3D human pose detection studies using the approaches of HPDM, HPDFLML, HPDMF, HPDDS, and HPDMK in addition to detection of the suggested method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment performs 3D human pose detection studies using the approaches of HPDM, HPDFLML, HPDMF, HPDDS, and HPDMK in addition to detection of the suggested method.…”
Section: Resultsmentioning
confidence: 99%
“…In another context, He and Li demonstrated a Kinect-based method for identifying human posture. Their method includes utilizing Kinect to determine the coordinates of joints.…”
Section: Introductionmentioning
confidence: 99%
“…The explanation is that athletes with a high athletics level have more detailed information about mental training techniques, and some of them, therefore, use these methods. (He et al, 2020) suggested a Kinect-based posture recognition method (KPRM) for Physical Sports Training Based on Urban Data. Kinect firstly uses the spatial coordinates of human body joints.…”
Section: Significance Of Student Sports Trainingmentioning
confidence: 99%